2003
DOI: 10.1046/j.1526-0968.2003.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Apheresis on Adhesion Molecules

Abstract: The adhesion molecules on the leukocytes and the endothelial cells mediate interaction between their cells. The plasma levels of soluble adhesion molecules increase in patients with ischemic heart disease, atherosclerotic aortic disease. Hypercholesterolemia is one of risk factors for atherosclerosis, and it is considered that the expression of adhesion molecules in endothelial cells is related to the development of atherosclerosis. Low-density lipoprotein (LDL) apheresis has been applied to patients with hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In our own experience only DALI improved the cerebrovascular CO 2 reactivity, whereas HELP or LF did not [16]. Selective LDL adsorption simultaneously removes circulating soluble adhesion molecules, such as sICAM-1 and sVCAM-1, P-selectin, E-selectin, TNFα and monocyte chemoattractant protein (MCP)-1 [17][18][19][20][21][22][23][24][25][26]. In a comparison of different LDL apheresis methods the effects on adhesion molecules were seen after DALI, DSA and HELP [26].…”
Section: Effects Of Ldl Apheresis On the Vascular Systemmentioning
confidence: 99%
“…In our own experience only DALI improved the cerebrovascular CO 2 reactivity, whereas HELP or LF did not [16]. Selective LDL adsorption simultaneously removes circulating soluble adhesion molecules, such as sICAM-1 and sVCAM-1, P-selectin, E-selectin, TNFα and monocyte chemoattractant protein (MCP)-1 [17][18][19][20][21][22][23][24][25][26]. In a comparison of different LDL apheresis methods the effects on adhesion molecules were seen after DALI, DSA and HELP [26].…”
Section: Effects Of Ldl Apheresis On the Vascular Systemmentioning
confidence: 99%
“…Our data have shown that all the hyperviscosity factors were decreased significantly (25). After rheopheresis it was shown that transcutaneous oxygen saturation was much more significant, meanwhile oxidative stress (15) and adhesive molecules (14) were decreased substantially. Microcirculation should be changed dramatically after post‐aggregated pollution is swept out from the damaged vessel of diabetes milieu (14,19).…”
Section: Discussionmentioning
confidence: 55%
“…Two patients had contracted kidney with lobulation at the surface, which was proved by Doppler ultrasonography as not due to renal artery stenosis. They were treated with rheopheresis or EC‐40W (Asahi Kasai), which was used here as a plasma fractionator and cut off protein greater than IgG, so that fibrinogen and all of the above molecules would be impacted (14,15). Our data have shown that all the hyperviscosity factors were decreased significantly (25).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Subsequently, attempts were made to remove LDL selectively [46,47] and several techniques for selective removal of LDL, termed LDL apheresis, are in current use: immunoadsorption, dextran sulphate-cellulose adsorption (DSA), heparin extracorporeal LDL precipitation system (HELP) and direct adsorption of lipoprotein using haemoperfusion (DALI). Comparison of these methods [48][49][50][51][52] In addition to, or perhaps because of, the profound cholesterol-lowering effects of LDL apheresis, several other potentially beneficial phenomena have been documented: decreased oxidability of LDL [57], improved vascular endothelial function and haemorheology [58,59], reduction in lipoprotein (a) and procoagulatory status [48,60,61], decrease in adhesion molecules [62,63] and C-reactive protein [64 . ]. The extent of changes in these non-LDL cholesterol parameters depends on the method used for extracorporeal LDL elimination.…”
Section: Aims and Age Of Initiation Of Treatmentmentioning
confidence: 99%